Quorum quenching by Est816: a novel approach to control Porphyromonas gingivalis pathogenicity - Zelda Ziyi Zhao; Lifeng Guo; Xiangyang Li; Tianfan Cheng; Chun Hung Chu; Jing Zhang (BMC Oral Health)
Abstract Background Porphyromonas gingivalis (P. gingivalis), a keystone pathogen in peri-implantitis, employs quorum sensing (QS) via N-acyl homoserine lactones (AHLs) to regulate biofilm formation and virulence. Quorum-quenching enzymes, such as the AHL-lactonase Est816, offer a promising therapeutic strategy to disrupt microbial pathogenicity. This study investigated the anti-biofilm, anti-virulence, immunomodulatory, biocompatibility, and osteogenic properties of Est816 against P. gingivalis, exploring its therapeutic potential for peri-implantitis management. Methods P. gingivalis (ATCC 33277) was cultured on titanium discs and treated with Est816 (P. gingivalis + Est816). Biofilm morphology, biomass, viability, and kinetics were assessed using scanning electron microscopy (SEM), crystal violet staining, confocal laser scanning microscope (CLSM), and colony-forming unit (CFU) counting. Exopolysaccharide (EPS) production was quantified via phenol-sulfuric acid assay, while virulence gene expression was analyzed by RT-PCR. Cytotoxicity of Est816 on human oral keratinocytes (HOKs) was assessed using immunofluorescent microscopy. The immunodulatory impact of Est816 on P. gingivalis infected human periodontal ligament stem cells (PDLSCs) was assessed via ELISA and RT-PCR. Osteogenic differentiation of PDLSCs was examined by alizarin red staining. Results Est816 treatment disrupted biofilm architecture (SEM), reducing biomass (crystal violet: 88% decrease, p < 0.001), viability (CLSM: live/dead ratio 0.3 vs. 5.7 control, p < 0.05), and CFU counts (2.8-log reduction, p < 0.001). EPS production decreased by 44% (p < 0.01), and virulence gene expression was significantly suppressed (rgpA: 80%, kgp: 76%, fimA: 73%, p < 0.01). Est816 exhibited no cytotoxicity toward HOKs and attenuated pro-inflammatory cytokine secretion in PDLSCs (TNF-α: 2.4-fold, IL-1β: 2.3-fold, IL-6: 11-fold, IL-8: 14-fold, reduction, p < 0.05). Furthermore, Est816 alone had no effect on the osteogenic differentiation of PDLSCs; however, it abolished the inhibitory effect of AHLs, significantly enhancing mineralized nodule formation by 1.4-fold (p < 0.001) compared to the AHL-treated control. Conclusion Est816 exhibited anti-biofilm property, attenuated virulence release in P. gingivalis, and counteracted AHL-mediated suppression of osteoblast differentiation in PDLSCs, highlighting its dual therapeutic role in both pathogen inhibition and host tissue regeneration for peri-implantitis.